Microsoft Forefront UAG 2010 Administrator's Handbook. - Ben-Ari, Erez (Packt Pub., 2011)
Take full command of Microsoft Forefront Unified Access Gateway to secure your business applications and provide dynamic remote access with DirectAccess with this book and eBook.